High-Reynolds-number wall-modelled large eddy simulations of turbulent pipe flows using explicit and implicit subgrid stress treatments within a spectral element solver. (15th September 2019) - Ferrer, E.; Saito, N.; Blackburn, H.M.; Pullin, D.I.
Highlights: Explicit and implicit large eddy simulations for turbulent pipe flows. Both models implemented in a high order continuous-Galerkin spectral element solver. Favourable results for pipe flows at Re tau = 2 × 10 3 and Re tau = 1.8 × 10 5 . The wall model in the implicit scheme enables lower levels of artificial dissipation. Abstract: We present explicit and implicit large eddy simulations for fully developed turbulent pipe flows using a continuous-Galerkin spectral element solver. On the one hand, the explicit stretched-vortex model (by Misra and Pullin [45] and Chung and Pullin [14]), accounts for an explicit treatment of unresolved stresses and is adapted to the high-order solver. On the other hand, an implicit approach based on a spectral vanishing viscosity technique is implemented. The latter implicit technique is modified to incorporate Chung & Pullin virtual-wall model instead of relying on implicit dissipative mechanisms near walls. This near-wall model is derived by averaging in the wall-normal direction and relying in local inner scaling to treat the time-dependence of the filtered wall-parallel velocity. The model requires space-time varying Dirichlet and Neumann boundary conditions for velocity and pressure respectively. We provide results and comparisons for the explicit and implicit subgrid treatments and show that both provide favourable results for pipe flows at R e τ = 2 × 10 3 and R e τ = 1.8 × 10 5 in terms of turbulence statistics. Additionally, we conclude that implicit simulations are enhanced when including the wall model and provide the correct statistics near walls.